Phylogeny reconstruction of the Schoeneae (Cyperaceae) with a focus on southern African genera - Henning, Jessica (Department of Biological Sciences, 2017)
In this study both plastid and nuclear DNA sequences (rbcL, trnL-trnF, rps16, ITS and ETS) were analysed. New sequences were added to the matrix from Verboom (2006). Parsimony method was used for phylogeny reconstruction. Morphological characters were then optimised on the parsimony tree using both maximum likelihood and parsimony reconstruction. The Schoeneae is not monophyletic. Scleria may be included in the Schoeneae. Schoenus is probably not monophyletic as was suggested by morphological heterogeneity. It seems as though the Schoeneae ancestor probably had present leaf blades, leaves spread out wide along the stem and an open inflorescence. Further research needs to be done including the sampling of more taxa and more sequences. The monophyly of this tribe is still yet to be resolved. Lower taxonmic relationships need to be resolved further.